2010
DOI: 10.3390/molecules15042326
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Biological Properties of Rhododendron anthopogon Essential Oil

Abstract: Abstract:The essential oil of Rhododendron anthopogon was investigated by GC-MS, and seventeen compounds (representing approximately 98% of the oil) were identified. The major components of the aerial parts of the oil were the monoterpenes α-pinene, β-pinene, limonene and the sesquiterpene δ-cadinene. Biological studies revealed a weak topical anti-inflammatory activity; a significant killing effect against some Gram-positive reference strains: Staphylococcus aureus, Enterococcusfecalis, Bacillus subtilis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…24 Usually, biological activity is assigned to major compounds. 25 The dominant group of compounds in B. tripartita root essential oil is the monoterpene hydrocarbons, with a-pinene as a main compound. Some studies have demonstrated good bacteriostatic and fungistatic properties of a-pinene, although some data show its low antimicrobial activity.…”
Section: Antimicrobial and Antifungal Activities Of The Essential Oilmentioning
confidence: 99%
“…24 Usually, biological activity is assigned to major compounds. 25 The dominant group of compounds in B. tripartita root essential oil is the monoterpene hydrocarbons, with a-pinene as a main compound. Some studies have demonstrated good bacteriostatic and fungistatic properties of a-pinene, although some data show its low antimicrobial activity.…”
Section: Antimicrobial and Antifungal Activities Of The Essential Oilmentioning
confidence: 99%
“…The essential oil of Rhododendron anthopogon was investigated by Innocenti et al (2010). The anti-microbial activity of R. anthopogon essential oil was evaluated by reference microdilution assays against a series of Gram-positive and Gram-negative reference strains.…”
Section: Figurementioning
confidence: 99%
“…Recently, there has been growing interests to find antimicrobial compounds from medicinal plant extracts as an alternative approach to discover new antimicrobial compounds (Ríos and Recio, 2005;Radji et al, 2013). Rhododendron species have been proved to possess medicinal and health promotion properties, including the ability to inhibit the growth of some types of pathogenic bacteria (Innocenti et al, 2010;Silici et al, 2010;Popescu and Kopp, 2013;Rezk et al, 2015;Wang et al, 2015;Li et al, 2016;Hakeem Said et al, 2017;Shrestha et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of herbs for the prevention and treatment of disease has been practiced for thousands of years in various countries, including China, Japan and Korea (1,2). Particularly in cancer treatment, polyherbal Chinese traditional medicine (TCM) formulas are widely used as an adjuvant therapy to surgery, chemotherapy and radiotherapy (3,4). Certain TCM herbs and formulas have previously been reported to target cancer by regulating immune function, inhibiting angiogenesis, inducing apoptosis and reversing the multi-drug resistance of tumor cells (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%